2009
DOI: 10.1200/jco.2008.21.4163
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Pathologic Complete Responses in Aggressive Stages II to III Breast Cancers With Every-4-Week Carboplatin and Weekly Paclitaxel With or Without Trastuzumab: A Brown University Oncology Group Study

Abstract: Neoadjuvant carboplatin and weekly paclitaxel +/- trastuzumab achieve high pCR rates in patients with HER2-positive and triple-negative disease without exposure to an anthracycline. Preliminary RFS results are encouraging but are likely influenced by adjuvant therapy received. Additional study of this regimen in high-risk patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 49 publications
1
63
1
2
Order By: Relevance
“…Neoadjuvant trastuzumab plus chemotherapy demonstrated a significant increase in pCR rates (15.7% vs. 31.7%; P < 0.001). pCR rates with neoadjuvant trastuzumab and anthracycline-free regimens in other studies range from 11% to 76% 22,24,25,[30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant trastuzumab plus chemotherapy demonstrated a significant increase in pCR rates (15.7% vs. 31.7%; P < 0.001). pCR rates with neoadjuvant trastuzumab and anthracycline-free regimens in other studies range from 11% to 76% 22,24,25,[30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have examined the potential benefits of concurrent trastuzumab in combination with anthracycline-based 11,12,[18][19][20][21] or non-anthracycline-based neoadjuvant therapy [22][23][24][25][26][27][28][29] in HER2-positive breast cancer, with reported pCR rates of up to 76% 30 . In this retrospective non-randomized study, we showed that while TCH is active, trastuzumab combined with a taxane and then with an anthracycline (PH-FECH) shows higher pCR rate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gene-expression profiling of breast cancer in the early 2000s suggested that TNBC shares molecular features with basallike BRCA-1 tumors, and TNBC is likely to be sensitive to DNA cross-linking agents such as cisplatin (15). Subsequently, various small neoadjuvant trials testing cisplatin observed a high path CR rate with platinum therapy suggesting it merits further evaluation (16,17 (19)(20)(21). In contrast, the phase III neoadjuvant trastuzumab trial, NOAH, enrolled 334 patients and successfully demonstrated that neoadjuvant trastuzumab in combination with chemotherapy resulted in a significantly higher path CR rate (43% vs. 23%, P ¼ 0.002) than chemotherapy alone (22).…”
Section: Rationale For Drug Development In the Neoadjuvant Settingmentioning
confidence: 99%
“…Most importantly, BRCA1 hypermethylation proves to be a predictor of longer time to relapse and improved OS in ovarian cancer patients undergoing chemotherapy with cisplatin [39] . Under this perspective single agent cisplatin NACT resulted in pCR in 21% of patients with TNBC [40] , while carboplatin and taxane combinations resulted in even greater response rates [41,42] . Despite taxane-and anthracycline-based regimens remain the mainstay for TNBC neoadjuvant treatment, these encouraging results indicate that carboplatin-taxane regimens could be a very efficacious non-anthracycline containing combination.…”
Section: Neoadjuvant Chemotherapy In Tnbcmentioning
confidence: 99%